Technology Blueprint Drying Rack Pulley System / Siti Nabilah Ruslin - Ruslin, Siti Nabilah (2020)
NR Tech is a manufacturing company that intends to be based in Taiping, Perak and established for the purpose of provides customers with full satisfaction. We also intend to produce a variety of technology-based products for the convenience of future customers. Our vision is to be the leading manufacturing company in furniture market as well as the whole of the United States will be achieved as we have put together the best strategies to ensure that these goals and missions are achieved. To this end, we have employed the best professionals who have the necessary vast experience needed to run and grow the business. We intend to ensure that our professionals become the best in the field by constantly offering training them to upgrade their skills.